(untitled) (Journal of Politics and International Studies, 2024)
This research views growing hyper-nationalism in India from a historical context till its culmination under the Modi regime. For this purpose, the study has been divided into three phases; narrative building, pre-partition, and post-partition. The research argues that hyper-nationalism and chanting of Hindutva under the Modi regime in India is not a new phenomenon, but rather deeply rooted in the Indian strategic culture since Chanakya. Moreover, it contends that India's strategic culture is formative and the study endeavors to develop a contextual analysis of Chanakya’s strategic thought and its relevance in India 2.0. Moreover, it has also been argued that how the idea of superiority was constructed through academic discourse, by orthodox Hindus. Furthermore, this research takes a deep insight into India’s bandwagoning with major global actors like the U.S. and Russia to counter China and argues that India’s philosophy of non-alignment and peace-loving nation is based on contrast in theory and practice. This study is descriptive in nature and critically elaborates on how Hindutva has been used as a means to an end in India 2.0 under the Modi regime and indicates that this hyper-nationalism is driven by history and takes its roots from Chanakya’s view on strategic culture.